2013
DOI: 10.1021/jp4004664
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT-D Studies of the Molecular Organic Energetic Material RDX

Abstract: EPSRC's High End Computing Programme. We acknowledge the support of the Diamond Light Source, STFC, and the ISIS Neutron and Muon Facility. Supporting information:The remaining DSC thermograms for β-RDX (Figures S1−S4); a comparison between the calculated lattice parameters and unit cell volumes for α-and γ-RDX, compared to previous DFT-D studies as well as relevant experimental data ( Figures S5 and S6); comparison of predicted INS spectra for α-RDX to those for γ-and ε-RDX at similar pressures ( Figures S7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 68 publications
8
58
1
Order By: Relevance
“…The last value is likely affected by the presence of mode ν44 . These values are somewhat higher than the typical value reported for FOX-7 (4.65 cm -1 ) 12. This suggests that the modes coupling in TKX-50 is somewhat stronger than in FOX-7.…”
contrasting
confidence: 56%
“…The last value is likely affected by the presence of mode ν44 . These values are somewhat higher than the typical value reported for FOX-7 (4.65 cm -1 ) 12. This suggests that the modes coupling in TKX-50 is somewhat stronger than in FOX-7.…”
contrasting
confidence: 56%
“…5 The importance of molecular crystals has lead to various computational approaches being employed to understand and elucidate their properties. While crystal-structure prediction and pharmaceuticals are very active and important areas of research, 6,7 many computational studies have also focused on energetic materials, 8,9 proton-transfer systems, 4,10 vibrational properties such as phonons and thermal displacement parameters, 11,12 as well as electronic properties. 13 The methods employed range from tailor-made force fields 8 to generic force fields such as OPLS 14 and CHARMM 15 to firstprinciples methods such as density-functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…The critical temperature of thermal explosion (T b ) is an important parameter to evaluate the thermal stability of an energetic compound because it is essential to insure the safe storage and process operations involving explosives, propellants, and pyrotechnics. [20,21] The value of T b of 558.5 K can be calculated by the following Equation (8): [22] T b = (E 0 -ΊE 0 2 -4E 0 RT p0 ) / 2R (8) where E 0 is the apparent activation energy obtained by Ozawa's method, R is the gas constant, and T p0 is the peak temperature corresponding to βǞ0, 551.3 K. The distribution of electronic density is an important indicator to express the chemical and physical properties of a molecule, [23] and the contour line map of the electronic density on compound A was drawn in Figure 4 using the Multiwfn program. [24] It is reported that heavy nucleus always possess high peaks due to the nuclear charge improving electron aggregation and then displays integral exponential attenuation towards all surrounding atoms.…”
Section: Articlementioning
confidence: 99%